Four-band non-Abelian topological insulator and its experimental realization - Tianshu Jiang (Nature Portfolio, 2021)
Non-Abelian topological insulators receive increasing attention due to entangled bulk bandgaps different from Abelian counterparts. Here, the authors realize two new classes of topological charges characterizing of a four-band non-Abelian topological insulator.